Retarded Mental Development in the Practice of Comprehensive Psychological and Psychiatric Expertise of Juvenile Offenders - Badmaeva V.D.; Oshevsky D.S.; Fedonkina A.A. (Психология и право, 2019)
The article is devoted to the problem of retarded mental development of juvenile offenders in forensic practice. The findings of male juvenile offenders (n = 30) who underwent a complex psychological and psychiatric expertise were analyzed. As a result of the study, a criminal-relevant pathopsychological symptom complex was identified in juvenile offenders with retarded mental development on organically imperfect soil. Violations manifest themselves in cognitive, emotional-volitional and personal spheres. They lead to a significant decrease in the level of arbitrary regulation, disrupting critical and prognostic functions, and deprive the minor during the time of the tort the ability to recognize and control the actual nature and public danger of his actions. In addition, partial retardation of mental development characteristic of juvenile defendants with personal immaturity without mental disorder is defined.